Sabotaged - Haddix, Margaret Peterson (Haddix, Margaret Peterson. Missing, 2011)
Time-travelers Jonah and Katherine are summoned to help another missing child from history, this time Virginia Dare from the Roanoke Colony, but their journey is sabotaged and goes dangerously awry, leaving them in the wrong time period. Includes author's note about the history of Roanoke Colony and Virginia Dare.